Assessing patient safety implementation and its associate factors in a pediatric inpatient ward - Rukmini, Rukmini; Qomariah, Siti Nur; Savage, Eileen (Universa Medicina, 2024)
BackgroundPatient safety is an emerging healthcare discipline with the ultimate goal of reducing errors and harm to patients by implementing quality health services. The provision of patient safety is complex and difficult to achieve. The purpose of this research was to assess patient safety in hospital pediatric inpatient care and factors affecting nurses implementing pediatric patient safety. MethodsThis cross-sectional study involved 80 nurses (male and female) at several private and public hospitals in Surabaya City. The research instruments used were secondary data on patient safety in hospital pediatric inpatient wards, hospital medical records, as well as questionnaires, and observations of the implementation of pediatric patient safety goals. Data were analyzed using multiple logistic regression. ResultsMost participants were female (71.3%), were over 45 years old (18%), and had more than 5 years of work experience in pediatric wards (76%). There were reportedly 145 patient safety incidents, consisting of 46% unexpected events (Kejadian Tidak Diharapkan), 48% nearly injurious events (Kejadian Nyaris Cedera), 6% potential injurious events (Kejadian Potensial Cedera), and 0% sentinel events. Multiple logistic regression analysis showed that nurses who work in less positive working settings are at higher risk of negative implementation of pediatric patient safety than those who work in positive working settings [AOR= 1.85 (95% CI 1.62-4.92)]. ConclusionThis study demonstrated that work setting and frequency of reported events were significantly associated with negative implementation of pediatric patient safety. Therefore, intervention is recommended to minimize unnecessary pediatric patient harm.